Hydrogen in R2Fe17 intermetallic compounds: structural, thermodynamic and magnetic properties - COEY, JOHN MICHAEL DAVID (American Physcial Society, 1997)
The absorption and diffusion behavior of hydrogen in iron-rich rare-earth intermetallics of the type R2Fe17 (R5Y, Sm, Gd! and the resulting changes of their magnetic properties are investigated. Intermediate hydrogen concentration indicate the solid-solution character of the hydrides. From equilibrium and nonequilibrium absorption experiments net reaction energies, bulk diffusion constants, and surface barrier energies for Sm2Fe17 are determined and discussed. The low-temperature quantum diffusion is discussed for the hydride and the corresponding nitride. The interstitial modification changes drastically the crystalline electric field in the rare-earth intermetallics. For Sm2Fe17H4 the crystalline electric-field parameter A205110 Ka0 22 is estimated from the anisotropy constants K1 and K2.
PUBLISHED
Keywords: Physics